Pivotal Study of a Novel Motor-Driven Endoscopic Ablation System - Schmidt, Boris; Petru, Jan; Chun, K R Julian; Sediva, Lucie; Bordignon, Stefano; Chen, Shaojie; Neuzil, Petr (Circulation. Arrhythmia and electrophysiology, 2021)
[Figure: see text].
Keywords: Operative Time; Recurrence; Male; doba přežití bez progrese choroby; Endoscopes; atrial fibrillation; Equipment Design; laser; Heart Rate; Aged; Case-Control Studies; Prospective Studies; mužské pohlaví; senioři; srdeční frekvence; Catheter Ablation; recidiva; design vybavení; Atrial Fibrillation; Pulmonary Veins; Time Factors; catheter; Endoscopy; akční potenciály; lidé; Action Potentials; ženské pohlaví; studie případů a kontrol; Humans; časové faktory; délka operace; venae pulmonales; pulmonary vein; endoskopie; katetrizační ablace; Female; Progression-Free Survival; lidé středního věku; endoskopy; fibrilace síní; Middle Aged; prospektivní studie